Analisis Penggunaan Bahasa Gaul dalam Percakapan antar Mahasiswa di Lingkungan Program Studi Pendidikan Bahasa dan Sastra Indonesia (Kajian Sosiolinguistik) - Mira, Ningsi; Djuli, Labu; Makan Malay, Narantoputrayadi (Jurnal Lazuardi, 2025)
This study is entitied "Analysis of the Use of Slang Language in Conversation among Students in the Indonesian Language and Literature Education Study Program (Sociolinguistic Study)". This study aims to determine how slang language is used in conversations among students in the Indonesian Language and Literature Education Study Program at Nusa Cendana University Kupang. The theory used in this research is Sociolinguistic Theory. The method used in this research is qualitative method. Data collection techniques used in this research are interview, documentation, note-taking, and voice recording techniques. Based on the data and research results obtained, there are 21 forms of slang language utterances divided into five analyses, namely: 5 forms of abbreviation (mo, su, bro, kek and gimana), 6 forms of acronyms (WA, HP, PHP, BTW, SKS and OMG), 4 forms of acronyms (curhat, matkul, mager and maba), 4 forms of inversion (kuy, takis, woles and sabi), and 2 forms of creative language (gabut and rempong).